O caleidoscópio do processo de saúde e doença na percepção de professores do ensino médio dos colégios públicos do município de Cascavel/Pr - Campos, Terezinha Aparecida (2018)
To understand part of the vast and complex universe of health and illness, it is necessary, first of all, humility to recognize that any study of this theme is partial and provisional. Second of all it is necessary to choose paths and cutouts to approach it. Initially, we sought to contextualize some aspects of the historical, social, economic, political, environmental and cultural moment in which the society finds itself. This contextualization is necessary because health and illness do not represent the same thing for people, since several factors can influence the imaginary of each one. This will depend on the time, on the place in which one lives, as well as on their social relations, on their individual and collective values, on scientific, religious, philosophical and daily conceptions. In this perspective, this study, through exploratory and qualitative field research, has as central objective to apprehend the perception of high school teachers of public schools from the city of Cascavel, Paraná, Brazil, on health and illness process in work. For the data collection, a semi-structured script was used, applied in the form of interviews and, later, the data obtained were grouped and analyzed through the Content Analysis Technique. It is inferred that teachers are exposed to an overload of work activities, double working hours, instability, professional, social and wage devaluation, besides the unhealthy conditions in the work environment. It was found that 66.7% of the teachers interviewed carry out their work activities during the morning and afternoon, and that 53.3% of them have a 40-hour workload per week, which represents an exhaustive working day, also because they are likely to perform other functions that are not tied to teaching, such as housewives, parents, mothers, and spouses. In this context, they often end up falling ill and, consequently, having to go to work even sick. It is so that 100% of respondents say that they have already worked sick. In the health problems reported it is included musculoskeletal disorders, migraines, voice problems, upper respiratory infections, and stress. It is inferred that adverse working conditions resulting from professional devaluation, inadequate physical structure, excess of students in class, double journey and work overload, among others, are causes that lead to the sickness of the teachers. Faced with this complexity that is this kaleidoscope of health and illness process, it was verified that this phenomenon extrapolates the physical and biological body, affecting their mental, social and cultural dimension, perceptible in their relations in the classroom and in their style and quality of life. It is considered that the health and illness process involves objective and subjective characteristics of human being. Thus, when looking at this subject, it is also necessary to consider the context, in which it is inserted, as well as its values, beliefs, senses and perceptions, in order to plan and promote actions aimed at reducing vulnerabilities and health risks in work environment.